An unusual spell of late night and morning Fog at Agartala Airfield and some associated features - BANERJEE, A. K.; SARKAR, C. S.; SEN, S. R. (MAUSAM, 1963)
The intense spell of fog which occurred at Agartala during the last week of December 1961 has been analysed from different angles and the characterstics presented. The meteorological conditions which led to its formation have been discussed. The diameter of fog particles as calculated from coronol measurements has also been worked out.